Creep behavior of compact γ′-γ′′ coprecipitation strengthened in718-variant superalloy - Mukhopadhyay, Semanti; Sriram, Hariharan; Zenk, Christopher; Didomizio, Richard; Detor, Andrew J.; Hayes, Robert W.; Viswanathan, Gopal B.; Wang, Yunzhi; Mills, Michael J. (Metals, 2021)
The development of high-temperature heavy-duty turbine disk materials is critical for improving the overall efficiency of combined cycle power plants. An alloy development strategy to this end involves superalloys strengthened by ‘compact’ γ′-γ” coprecipitates. Compact morphology of coprecipitates consists of a cuboidal γ′ precipitate such that γ” discs coat its six 001 faces. The present work is an attempt to investigate the microstructure and creep behavior of a fully aged alloy exhibiting compact coprecipitates. We conducted heat treatments, detailed microstructural characterization, and creep testing at 1200◦ F (649◦ C) on an IN718-variant alloy. Our results indicate that aged IN718-27 samples exhibit a relatively uniform distribution of compact coprecipitates, irrespective of the cooling rate. However, the alloy ruptured at low strains during creep tests at 1200◦ F (649◦ C). At 100 ksi (689 MPa) load, the alloy fails around 0.1% strain, and 75 ksi (517 MPa) loading causes rupture at 0.3% strain. We also report extensive intergranular failure in all the tested samples, which is attributed to cracking along grain boundary precipitates. The results suggest that while the compact coprecipitates are indeed thermally stable during thermomechanical processing, the microstructure of the alloy needs to be optimized for better creep strength and rupture life.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Compact; Coprecipitates; Creep; ECCI; Grain boundary; IN718; Microstructure; Superalloy